KEANEKARAGAMAN JENIS JAMUR MAKROSKOPIS DI BUKIT WANGKANG DESA SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Zulpitasari, Melinda; Ekyastuti, Wiwik; Oramahi, H A (Universitas Tanjungpura, 2019)
Macroscopic fungi important role for ecosystem sustainable forest. Research to diversity of species macroscopic fungi in area Bukit Wangkang, Sungai Ambawang village. The research was counducted by survey method with multiple plot techniques. Laying of plots by means of purposive sampling, plots measuring 5m x 5m. obtained 23 plot observations total area of 0,0575 Ha, total research area of 3700 Ha. The research area, found 29 macroscopic fungi from 13 families, the families polyporaceae many of 10 species, then hymenochaetaceae many of 4 (four) Â types and ganodermataceae many of 3 (three) types. The high INP value Mycena sp (26,571), Xylaria sp 1 (23,3312) and Xylaria sp 2 (13,8331). Discovered 8 (eight) species macroscopic fungi can be consumed such as ganoderma lucidum as medicinal ingredient which processed of powder and Lentinus tigrinus as food ingredients boiled or sautÃ©ed. Macroscopic fungi cannot be consumed like rigidoporus microporus because it has fruiting body that is hard, and poisonous fungi species such as coltricia sp and microporus sp types used as souvenir. 29 species of fungi founded 4 (four) species fungi grow out of the ground and 25 species types other in dead wood. Obtained 23 plots with three types of canopy density where density rarely obtained 6 (six) species of macroscopis fungi of 4 (four) plot, then density obtained 10 of fungi of 9 (nine) plot observation. Density obrained 13 fungi of 10 plot observations.Keywords: Edible mushroom, Macroscopic fungi, Secondary forest